MANAJEMEN PENGELOLAAN DAN PENGEMBANGAN ETIKA BISNIS DALAM PERUSAHAAN - Sofyan Hamid (AkMen JURNAL ILMIAH, 2012)
decision makers have the same position, and act fairly in providing services to customers either individually or in groups. Why is business ethics in the company feels is very important at this time? Due to form a strong company and has a highly competitive and has the ability to create value (value-creation) is high, we need a solid foundation. Usually starting from strategic planning, good organization, the system transparent procedures backed by a powerful corporate culture and ethics of the company that carried out consistently and consistently